Circular economy in fast fashion - the case of Zara - Oestereich, Eve-Meline Luise Verena (2024)
The case study examines the fast fashion industry’s journey towards a circular economy. For this purpose, it examines the brand Zara and its historical business model, which is focused on fast turnover and volume, and weighs this against the principles of circular economy. The study also delves into Zara’s initiatives, such as material sourcing, donation programs, and resale platforms, and highlights the challenges and contradictions with regard to circularity. The study encourages a discussion about the feasible potential of such a transition and questions the balance between commercial goals and environmental responsibility.